Cost of quality control to improve production cost efficiency and sales productivity (Case study on companies in Sidoarjo) - Achmad Daeng GS; Mahjudin .; Eka Tupiana (The Indonesian Accounting Review, 2014)
Companies require producing quality products at competitive prices. As a result, they should have an edge or more value than their competitors. This study aims to determine the optimal cost of quality control to be able to improve cost efficiency and productivity in the company. This study is using a qualitative approach. This case study is using interviews with managers and employees of the accounting firms to get information and documents. It shows that the companies have not yet reported the costof quality; neither did they set standards for the cost of quality. Beside they did not analyze the reports relating to the cost of quality. The companies expected to report the cost of quality in particular, apart from reports of production costs. In charge of quality control, the company expected to set the standard for the cost of quality that should be removed. Control over the cost of quality also should be accompanied by an increase in sales. Analysis on the cost of quality cost should be done so at the expense of quality control can improve cost efficiency and productivity of the Company.